PENGGUNAAN MODEL KOOPERATF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VII.1 DI SMPN 3 TANAH PUTIH - Trisnawati, Fenny; ', Rubiah; ', Sumarno (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: Student Teams Achievement Division or abbreviated with STAD is learning in which students are placed in study groups of four or five students which is a mix of academic ability is different, so that within each group there are students who are high achievers, medium, and low or variations of sex , racial and ethnic groups or other social groups. The goal of this research is to improve student learning outcomes IPS VII.1 class in SMPN 3 Tanah Putih. The sample in this study were students VII.1 SMP Negeri 3 Tanah Putih academic year 2015/2016, totaling 31 students, consisting of 18 male students and 13 female students. Data obtained using the technique written tests, observation and documentation. While data analysis techniques used are: student learning, the activities of teachers and students' activity. From the results of data analysis that has been done shows STAD cooperative learning model can improve learning outcomes in social studies classes in SMPN 3 VII.1 Tanah Putih. From these results it is expected that the school, paying attention STAD cooperative learning model can be used as an alternative in improving student learning outcomes, with more emphasis on the teacher's role in guiding and motivating students in learning groups. If the result of learning increases, the quality of schools also increased.Keywords:Model Cooperative Stad Method , learning outcomes and Economic